Optimization of seed rate and spacing in soybean (Glycine max L.): Optimization of seed rate and spacing in soybean (Glycine max L.) - D K KATHMALE; R N PALVI; S B MAHAJAN (Journal of Oilseeds Research, 2020)
To optimize seed rate and plant spacing in soybean an experiment was conducted with four plant spacings and three treatments of number of seeds dibbled. Sowing of soybean at 45 x 5 cm plant spacing with single seed dibbling (50 kg seed/ha) was beneficial for higher yields and economic returns in soybean.